When data changes pre-purchase behavior : the effects of information visualization on online information seeking - Casalinho, Gilmar D'Agostini Oliveira (2016)
Online consumer information search became a crucial initial step in the purchase decision process. The objective of this dissertation is to investigate and measure the effects of different visual representations of information about products on individual’s behavior during pre-purchase online information seeking activities. More specifically, this dissertation analyze what type of information customers considered most important and pays more attention and what is the extent of the visual aspect and its impact in information seeking behavior. To do so, five experiments were conducted, three using online participants via Amazon Mechanical Turk, and two using participants in a laboratory setting, being collected biological measures in one of them. Through two studies, the first article shows how different degrees of evaluability of the same online review can influence on helpfulness, overestimation of information, and purchase intention. It also evidence individual’s involvement while browsing has a moderating role in the relation between evaluability and helpfulness as well as in the relation between evaluability and purchase intention. The second article analyze the relationship between depth-of-field and type of search on several behavioral outcomes, such as intention do revisit the website and visual appeal. It was also investigated whether or not involvement, expertise and attitude toward products moderates these relations. Drawing on the findings of the first and second articles, the third article focus on replicate the finding of the second article via biological measures using an eye-tracking device, including attention measures. The third article aims to contribute to online information seeking literature by investigating participant’s online search and browse behaviors and the resulting processing of information when viewing products presented visually differently in a webpage. These patterns of individual’s visualization studied in both three articles have important practical implications for the website design creating experiences that supports the type of information search undertaken by consumers.